CERT System and Network Security Practices - SINGH, YASHWANT KUMAR; RATAWA, SURYA PRAKASH (IJRDO -Journal of Computer Science Engineering, 2017)
Networks have become indispensable for conducting business ingovernment,commercial, and academic organizations. Networked systems allow you toaccess needed information rapidly, improve communications while reducing their cost,collaborate with partners, provide better customer services, and conduct electroniccommerce. While computer networks revolutionize the way you do business, the risksthey introduce can be fatal to a business. Attacks on networks can lead to lost money,time, products, reputation, sensitive information, and even lives.Systems, networks, and sensitive information can be compromised by malicious andinadvertent actions despite an administrator’s best efforts. Even when an administratorknows what to do, they often don’t have the time to do it; operational day-to-dayconcerns and keeping systems functioning take priority over securing those systems.The knowledge that most system and network administrators have about protecting andsecuring systems typically comes from experience and word-of-mouth, not byconsulting a published set of procedures that serve in the role of de facto standardsgenerally accepted by the administrator community; these do not currently exist. For thisreason and others described in this paper, an administrator needs easy-to-access, easy-tounderstand,easy-to-implement security practices. The CERT system and networksecurity practices are intended to meet these needs.CERT security practices are organized into five top-level steps: Harden/Secure, Prepare,Detect, Respond, and Improve. A total of fifty current practices comprise these steps.They are summarized in this paper and fully documented on the CERT web site athttp://www.cert.org. The practices to harden and secure systems form a strongfoundation by establishing secure configurations of computing assets. Prepare, Detect,Respond, and Improve practices assumes that Harden/Secure practices have beenimplemented and provide further guidance on what to do when something suspicious,unexpected, or unusual occurs.